Effect of video-based collaborative peer feedback on Turkish EFL learners’ motivation, writing enjoyment and anxiety - Yeşilçınar, Sabahattin; Ekşi, Gonca Yangın (My University, 2024)
The existing literature generally acknowledges that students receive more feedback and detail when video feedback is used, but how writing feedback practices, in particular video feedback, influence learner affective factors is still a gap to be filled. Being grounded on the process writing theory and the social constructivist theory, this 14-week research investigated (i) the effect of video-based collaborative peer feedback (VCPF) on English as a foreign language (EFL) students’ writing motivation, anxiety, and enjoyment, (ii) students’ preference of using surface- and meaning-level feedback while providing VCPF, and (iii) their perception of using VCPF. The findings show that the use of VCPF increases learners’ writing motivation and enjoyment and decreases their anxiety. Although both types of feedback are preferred, learners mostly focus on conceptual academic skills (e.g., idea development, analysis, and synthesis). VCPF is considered a useful and an enjoyable application, which enables learners to provide more constructive recommendations and comments, rather than simply itemizing mistakes. This research advocates that VCPF is clear, informative and constructive, time saving, and more enjoyable. The results imply that VCPF is an effective method and is, therefore, eligible for classroom practice and for future research.
Keywords: Improving classroom teaching; Adult learning; Cooperative/collaborative learning